Dynamic Simulation to Minimize Inventory Cost of Coal Considering Uncertainty Demand of Product - Muyasaroh Effendi; Ahmad Rusdiansyah (IPTEK Journal of Proceedings Series, 2020)
This paper briefly discusses the inventory management of coal in a cement industry. The cement company uses coal as fuel in the production process. Continuous production process must be maintained, thus the coal supply must be met to the production demand. In this study, we develop a dynamic simulation of coal inventory control system. We implemented periodic review system (P system) and continuous review system (Q system) method. Our simulation scenario consider some decision variables such as supply, variation of demand, and fluctuation of demand in order to understand the behaviour of the proposed model. This method is expected to provide recommendations for improve the inventory control policies in determining the optimum amount of coal in the warehouse and the optimal interval between orders with a minimum total inventory cost at uncertainty demand condition of product clinker and cement.